Analisis Implementasi Green Economy pada Usaha Mikro, Kecil, dan Menengah (UMKM) - Fenny Noor Salam; Dinda Ayu Izmi; Devi Trenggani (Universitas Ngudi Waluyo, 2026)
The implementation of a green economy in Micro, Small, and Medium Enterprises (MSMEs) is a strategic step toward balancing economic growth and ensuring environmental sustainability. This study aims to analyze the influence of policy factors, technology and investment factors, and social and behavioral factors on the implementation of a green economy in MSMEs in Bandung Regency. A quantitative research approach was used. Data were collected through a questionnaire distributed to 100 MSME respondents selected using purposive sampling. Quantitative data analysis was conducted using multiple linear regression analysis with SPSS version 25. The results of the regression analysis indicate that Policy Factors (t = 3.603, p < 0.05), Technology and Investment Factors (t = 3.202, p < 0.05), and Social and Behavioral Factors (t = 2.584, p < 0.05) each have a positive and significant partial effect on the implementation of the green economy. The Policy Factor has a regression coefficient of 0.213, the Technology and Investment Factor of 0.297, and the Social and Behavioral Factor of 0.275. These findings confirm that synergy between supportive government regulations, readiness to adopt environmentally friendly technologies, capital support, and shifts in public consumption behavior are key to the success of the green transformation in the MSME sector. Abstrak Implementasi green economy pada Usaha Mikro, Kecil, dan Menengah (UMKM) menjadi langkah strategis dalam menyeimbangkan pertumbuhan ekonomi dan menjaga keberlanjutan lingkungan hidup. Penelitian ini bertujuan untuk menganalisis pengaruh Faktor Kebijakan, Faktor Teknologi dan Investasi, serta Faktor Sosial dan Perilaku terhadap Implementasi Green Economy pada UMKM di Kabupaten Bandung. Pendekatan penelitian yang digunakan adalah metode kuantitatif. Data dikumpulkan melalui penyebaran kuesioner kepada 100 responden UMKM yang dipilih menggunakan teknik purposive sampling. Analisis data kuantitatif dilakukan menggunakan analisis regresi linear berganda melalui software SPSS versi 25. Hasil analisis regresi menunjukkan bahwa Faktor Kebijakan (t = 3,603, p < 0,05), Faktor Teknologi dan Investasi (t = 3,202, p < 0,05), dan Faktor Sosial dan Perilaku (t = 2,584, p < 0,05) secara parsial memberikan pengaruh yang positif dan signifikan terhadap Implementasi Green Economy. Faktor Kebijakan memiliki nilai koefisien regresi sebesar 0,213, Faktor Teknologi dan Investasi sebesar 0,297, serta Faktor Sosial dan Perilaku sebesar 0,275. Temuan ini menegaskan bahwa sinergi antara regulasi pemerintah yang suportif, kesiapan adopsi teknologi ramah lingkungan, dukungan modal, serta pergeseran perilaku konsumsi masyarakat menjadi kunci keberhasilan transformasi hijau pada sektor UMKM.